Health platformization, public interoperability, and territorial selectivity: the digitalized public health system and the role of the private NAV platform in the state of Rio de Janeiro, Brazil - Moreira, Gustavo Augusto (Geografares, 2026)
This article examines health platformization as a process of territorial and capitalist reorganization of care in Brazil, based on two distinct regimes of digitanization: on the one hand, the public construction of interoperability within the Unified Health System (SUS); on the other hand, the operation of NAV, the digital platformod Diagnósticos da América S. A. (Dasa), a private health group originally linked to diagnostic medicine and recently expanded inte integrated health service. The objective is to understand how data, interoperability, and platforms become strategic resources for coordination, command, and accumulation, articulation technique, regulation, the State, and the market. The article starts from the hypothesis that digital health is not merely a form of technical modernization, but a contemporary form of territorialization of informational power, wich recentralizes coordination, data, and command in selective points of space. Methodologically, the study combines theoretical review, documentary analysis, and territorial interpretation, drawing on documents and reports from the Ministry of Health, as well as operational and financial data, corporate reports from Dasa and survey of territorial distribution of its network in the state of Rio de Janeiro.
Keywords: health platformization; SUS Digital; NAV/Dasa; territorial selectivity; Rio de Janeiro